A Comparative Investigation of the Views of Preschool Teachers and Teacher Candidates about STEM - Neslihan ÜLTAY; Eser Ultay (Journal of Science Learning, 2020)
If the STEM approach appropriately addressed in early childhood education, it may provide opportunities for educators to involve children in activities appropriate to their interests and experiences. The purpose of this research is to investigate comparatively the views of preschool teachers and preschool teacher candidates about STEM. To collect data, 60 preschool teachers graduated from different universities in Turkey have different experiments and actively in the teaching profession in various schools in the years 2018 to 2019, and 65 preschool teacher candidates in the first, second, third and fourth grades in the 2018-2019 academic year at a state university in the region of the Black Sea randomly selected. To collect data, preschool teachers and teacher candidates ask to answer the questions in the Screening Form consisting of open-ended questions aimed at obtaining in-depth information about STEM education. The findings analyze in detail, and it seen that the answers of both groups can discuss under three main themes; (1) The effects of the STEM approach, (2) The applicability of the STEM approach in preschool education, and (3) The requirements of the applicability of the STEM approach in Turkish educational system. According to the findings, participants have positive views about implementing the STEM approach in their classes for the teachers and future professional lives for the teacher candidates. However, there are some limitations about implementing it arising from the infrastructure of the schools, the teachers themselves, and children’s young age.